2021
DOI: 10.1136/bmjopen-2021-049384
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based cognitive–behavioural therapy for tinnitus: secondary analysis to examine predictors of outcomes

Abstract: ObjectivesThe current study examined predictors of outcomes of internet-based cognitive–behavioural therapy (ICBT) for individuals with tinnitus.DesignSecondary analysis of intervention studies.SettingInternet-based guided tinnitus intervention provided in the UK.Participants228 individuals who underwent ICBT.InterventionsICBT.Primary and secondary outcome measuresThe key predictor variables included demographic, tinnitus, hearing-related and treatment-related variables as well as clinical factors (eg, anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Baseline tinnitus severity was found to be another critical factor for predicting ICBT outcomes in the GB model. Our previous studies on 1-year outcomes [ 53 ] and our previous application of univariate and multivariate analyses to this study’s sample [ 19 ] identified baseline tinnitus severity as a critical predictive variable. In the Niemann et al [ 21 ] study, tinnitus loudness, frequency, and distress, which were measured by using a visual analog scale, were found to be key predictive factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline tinnitus severity was found to be another critical factor for predicting ICBT outcomes in the GB model. Our previous studies on 1-year outcomes [ 53 ] and our previous application of univariate and multivariate analyses to this study’s sample [ 19 ] identified baseline tinnitus severity as a critical predictive variable. In the Niemann et al [ 21 ] study, tinnitus loudness, frequency, and distress, which were measured by using a visual analog scale, were found to be key predictive factors.…”
Section: Discussionmentioning
confidence: 99%
“…The predictors of outcomes that were identified when examining the long-term (1 year) outcomes of ICBT in the United Kingdom were higher baseline tinnitus severity, more engagement with the ICBT program (ie, more modules opened), and higher self-reported satisfaction with the intervention [ 18 ]. To further explore predictors of outcomes, various univariate and multivariate (ie, logistic and linear) regression models were applied to a combined data set of multiple ICBT studies [ 19 ]. These linear and logistic regression models identified education level (linear regression: P =.01; logistic regression: P <.001) and baseline tinnitus severity (linear regression: P <.001; logistic regression: P <.001) to be significant predictor variables that contribute to reductions in tinnitus severity following an ICBT intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reductions in tinnitus distress were greater for those with significant levels of depression at the bassline. Rodrigo et al ( 55 ) identified that the greater baseline tinnitus severity and those with greater educational levels were more likely to have a greater reduction in tinnitus distress after undertaking an ICBT intervention. The participants in this current trial represented those with higher levels of education as the majority had a university degree, college, or vocational training.…”
Section: Discussionmentioning
confidence: 99%
“…Although the affected patients receive a sensation of sound in the ear or the skull, they are unable to receive corresponding external stimulus or sound source [1][2][3]. A study has demonstrated that about 15 -19 % of people have experienced or have been experiencing tinnitus [4]. Clinical data show that people with a predisposition to tinnitus frequently manifest symptoms such as inattentiveness and poor sleep quality, and in severe cases, negative emotions such as irritability, depression and anxiety, all of which negatively affect quality of life and health [5].…”
Section: Introductionmentioning
confidence: 99%